DARI TRIBUN KE TAHTA: RELASI OLAHRAGA DAN KEKUASAAN - Carry Rafles Naibaho; Esra Olivia Siburian; Acen Chia Sin Laoly; Aziz Torang Junior Koto; Lata Christopel Siregar; Putri Enjel Martuani Sitorus; Bani pratama; Yan Indra Siregar; Putra Arima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the relationship between sports, politics, and power from the perspective of sports sociology. In modern society, sports are no longer viewed merely as physical activities and entertainment, but have developed into social and political instruments with significant influence on society. The purpose of this study is to analyze how sports are used as a tool of political legitimacy, a medium for shaping national identity, and an arena for contesting political influence in social life. The research method employed is qualitative research with a descriptive approach through library research. Data were collected from books, scientific journals, articles, and various literature sources related to sports, politics, and power. The findings indicate that sports have a very close relationship with political power. Governments and political elites often utilize sports as a means of image-building, strengthening legitimacy, and reinforcing nationalism within society. The involvement of political elites in sports organizations also demonstrates that sports have become a strategic arena for building social and political influence. On the other hand, the relationship between sports and power produces positive impacts such as social unity, infrastructure development, and international diplomacy, but also generates negative effects including corruption, match manipulation, fanaticism, and athlete exploitation. Based on these findings, it can be concluded that sports are not merely arenas of physical competition, but also social spaces filled with political interests and power relations in modern life.